Determination of void arrangements in inverse opals by transmission electron microscopy - Blanford, C; Carter, C; Stein, A (2006)
Three-dimensionally ordered macroporous (3DOM) materials, also known as inverse opals, have been extensively investigated for use as photonic crystals that operate in the visible and near-IR region of the spectrum. Because the template for 3DOM materials is made by a colloidal self-assembly process, they can easily incorporate defects that degrade or eliminate their desired light-restricting properties. We have developed a method that uses transmission electron microscopy (TEM) to probe the interior of individual sections of 3DOM photonic crystals by bright-field imaging followed by two-dimensional Fourier image analysis. The technique permits the viewing of stacking faults in the crystal. Analysis of samples of 3DOM ceramics has allowed us to confirm that the voids in the structures are arranged on the points of a face-centred cubic lattice.